Teres major isolated complete tear during routine gym workout: Case report and literature review - Muath Marghalani, MBBS; Roqaya Bamoharram, MBBS (Radiology Case Reports)
Teres major injuries are uncommon, presenting as sports related with the reported majority occurring in baseball players. Here we are presenting a case of compete teres major tendon tear in a hobbyist body builder during his routine workout session while practicing an overhead set. On examination, the patient had muscle retraction and swelling below the scapula with minor limitation of movement. MRI confirmed the complete tear of the teres major muscle at the musculotendinous junction with tendon retraction. Patient offered (type of treatment). He underwent conservative management with near complete recovery and returned to training within a 3 months period.